Design and Performance Analysis of a Wine-bridge RC Harmonic Oscillation Generator with an Operational Amplifier - Boyan Karapenev (IAES Indonesian Section, 2020)
This paper presents the special features of harmonic generators and their widespread use and in particular the design, simulation and experimental studies of a Wine-bridge RC generator with an operational amplifier. The results obtained are analyzed and compared. It can be deduced that the parameters of the output signal can be accurately realized - the necessary frequency and the amplitude by setting the parameters of the constituent components.